Economic and ecological characteristic of the phosphate raw material processing technology - Vasylinych, T. M.; Petruk, H. D.; Sakalova, H. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The economic efficiency and the value of avoided ecological damage due to the implementation of the phosphate raw material processing technology applying hydrosulphate method were calculated.